The Maisky diaries : Red ambassador to the Court of St James's, 1932-1943 - Maĭskiĭ, I. M. (Ivan Mikhaĭlovich), 1884-1975 (Yale University Press, 2015)
The terror and purges of Stalin's Russia in the 1930s discouraged Soviet officials from leaving documentary records let alone keeping personal diaries. A remarkable exception is the unique diary assiduously kept by Ivan Maisky, the Soviet ambassador to London between 1932 and 1943. This selection from Maisky's diary, never before published in English, grippingly documents Britain's drift to war during the 1930s, appeasement in the Munich era, negotiations leading to the signature of the Ribbentrop-Molotov Pact, Churchill's rise to power, the German invasion of Russia, and the intense debate over the opening of the second front. Maisky was distinguished by his great sociability and access to the key players in British public life. Among his range of regular contacts were politicians (including Churchill, Chamberlain, Eden, and Halifax), press barons (Beaverbrook), ambassadors (Joseph Kennedy), intellectuals (Keynes, Sidney and Beatrice Webb), writers (George Bernard Shaw, H.G. Wells), and indeed royalty. His diary further reveals the role personal rivalries within the Kremlin played in the formulation of Soviet policy at the time.